"A freak that no one can love": difficult knowledge in testimonials on school bullying. Issue 3 (3rd May 2020) - Tholander, Michael; Lindberg, Anna; Svensson, Daniel
ABSTRACT: This study adopts a testimonial approach to bullying victimisation, and aims to create a deeper understanding of the experiences and effects of being a bullying target. Four written narratives about being subjected to school bullying were analysed according to interpretative phenomenological analysis. From the analysis, four themes were constructed, which represented different elements of victimhood: (1) Self-blame in which victims view themselves as the cause of the bullying, (2) Abandonment in which victims describe feelings of standing alone in their exposed situation, (3) Turning points in which the victims recount a variety of restorative events, and (4) Continued victimhood in which the victims relate how the feeling of victimhood and vulnerability continues even though the bullying has ended. In conclusion, school bullying is something that continues to affect the individual adversely long after it has stopped, although stable friendship relations might have a mitigating influence. Through such relations, victimhood can be neutralised and a more positive self-image develop. Moreover, as numerous other kinds of victims emphasise, an essential part of the rehabilitation process is to finally be able to tell one's story, to lay bare one's difficult knowledge to a wider audience.